Analysis of university background and entrance exam performance of applicants to the Italian Hospital of Buenos Aires residency program: 2003-2006 - Eymann, Alfredo; Busaniche, Julio; Durante, Eduardo; Sadler, Alberto; Faingold, Diego; Figari, Marcelo; Carrió, Silvia (Revista del Hospital Italiano de Buenos Aires, 2006)
.